PERAN SISTEM INFORMASI MANAJEMEN DALAM MENINGKATKAN EFISIENSI KERJA DI PERUSAHAAN - Selvi Ayu Berutu; Muhammad Irwan Padli Nasution (CV. Barokah Publsiher, 2025)
The Management Information System (MIS) is a key strategic element for organizations in the digital age, functioning to process data into accurate information to support decision-making and competitiveness. This study utilizes a qualitative descriptive method to analyze the role of Management Information System (MIS) in enhancing work efficiency. The findings indicate that Management Information System (MIS) improves efficiency through process automation and facilitates superior data-driven decision-making. However, the implementation of Management Information System (MIS) faces significant obstacles, notably the limited availability of technological facilities and the lack of human resource (HR) competence in operating the system. The success of Management Information System (MIS) is highly dependent on adequate technological investment and the development of personnel skills..